ABKHAZ-ABAZIN DIASPORA IN EUROPE. SOME ISSUES OF PRESERVING THE TRADITIONAL CULTURE OF ABKHAZIANS AND ABAZINS ABROAD - Ajba, Tamara Guramovna (History, Archeology and Ethnography of the Caucasus, 2022)
The paper examines the history of the formation of the Abkhaz-Abazin diaspora in Europe and its main settlements in European states. The Abkhazians (Apsua) and Abazins (Abaza) abroad identify themselves as a single Abkhaz-Abazin (Abaza) ethnos, therefore, we discuss these two ethnic groups as one. As a result of the study, we have identified that the labor migrants (natives of the Caucasus) experienced partial assimilation in the receiving states, thus we pay special attention on the instruments, allowing the Abkhazians and Abazins to retain their traditional and cultural identity. An inevitable process of adaptation led to the loss of important ethnic components. Observing the negative impact of this process, an initiative part of the community has been trying to preserve the traditional culture (Apsuara, Abazara, Adyghe Khabze) and national languages in the context of modern reality. A significant support in this issue has been provided by the creation of the public organization “World Abkhaz-Abazin Congress” (WAAC). Summarizing the results of the study, we have managed to demonstrate the role and importance of WAAC for the European diaspora of Abkhazians and Abazins, directed at preserving the original culture of these two related ethnic groups.
Keywords: Abaza culture; apsua; diaspora; Europe; ethnos; self-preservation; identity.